ANALISIS DAN PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN SAWIT PADA PT. ANDALAN ALAM SUMATRA MENGGUNAKAN METODE FORWARD CHAINING - Kurniawansyah, Kevin; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
Palm oil is one of the plantations that are often attacked by disease. The disease of this planting plants isspread rapidly, so it must be in the culprit. To know the oil palm plant disease or not to be diagnosed tothe symptoms found in the field. At PT Andalan Alam Sumatra there are still many obstacles in perosesdiagnosis of oil palm disease, while the constraint that occurs is the lack of knowledge of employees ofpalm oil disease, still need help from plantation managers in diagnosing disease. Peroses diagnostics willbe hampered when plantation managers are not in place or being out of service, this also greatly burdenthe work of a planter manager. Because of peroses peroses diagnosis of palm oil disease disease perosesdisease prevention also become obstructed. As a result, palm oil disease spreads and disrupts theproductivity of oil palms, causing death in palm oil. Therefore it is necessary media that can helpovercome this as for medianya system of plant disease diagnosis by applying Forward Chaining method.This expert system of plant disease diagnosis using object-based modeling techniques to describe theanalysis and system design, namely in the form of use case diagrams, class diagrams, and activitydiagrams. The output of this research is the design of prototype system Analysis And Design ExpertSystem Diagnosis Disease Palm Plant At PT. Andalan Alam Sumatra With Forward Chaining Method